If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -12 = -133 Reorder the terms: -12 + 11y = -133 Solving -12 + 11y = -133 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 11y = -133 + 12 Combine like terms: -12 + 12 = 0 0 + 11y = -133 + 12 11y = -133 + 12 Combine like terms: -133 + 12 = -121 11y = -121 Divide each side by '11'. y = -11 Simplifying y = -11
| 7m-2=34+3m | | -11y=-55 | | 4(3+6X)-3=57 | | 12+y=23 | | 5x^3+10x^2-120x=0 | | -12y+5=65 | | (x+3)=(x-4) | | (4x^2+34x+44)/(x+7) | | 2*5x+5y+5y=2+5x*5y | | 4h^2+24h-133=0 | | 1+4g+5y*6y+5y=1+4gy+4g | | 1+4g+5y*6y=1+g | | (2/5r)=5+r*1 | | 2/(5r)=5+r*6h | | 2/5r=5+r*6h | | 1+.75r=1*.75r | | 1xy*1xy=1xy*5xy | | ln(x+2)+ln(2x+1)=0 | | 56x+13563788686867382937x= | | 10=(1800-2q)/43 | | 4x=18+7x | | 5x=15+8x | | 7x-18=3x+6 | | 6x=13+9x | | 4z-2=22 | | 4(2/5+6x) | | 3x=40+7x | | 9x-13=5x+7 | | 7x=13+8x | | 8x-15=2x+9 | | 4x=12+5x | | 2u^2(4-1)=0 |